Diagnosis and prognosis of congenital CMV infection: A case report and review of the literature. (August 2014) - Lazzarotto, Tiziana; Gabrielli, Liliana; Guerra, Brunella; Cervi, Francesca; Piccirilli, Giulia; Simonazzi, Giuliana; Chiereghin, Angela; Bellini, Francesca; Landini, Maria Paola
Abstract: Congenital cytomegalovirus (CMV) infection is the leading non-genetic cause of sensori-neural hearing loss and neurodevelopmental sequelae. Despite these alarming facts, the general public healthcare system is often not aware of CMV and not enough is done to prevent congenital CMV infection.We describe the clinical and laboratory monitoring of a case with primary CMV infection occurring before the first trimester of gestation. Specific literature review is included in order to point out major goals achieved in the diagnosis and prognosis of congenital CMV infection and the many questions still unanswered. Serological diagnosis of primary CMV infection was performed based on serum-CMV specific-IgM antibodies, combined with low avidity anti-CMV IgG antibodies. The maternal infection was asymptomatic, as it is for most infections in immunocompetent patients. Therefore, disclosing primary infection depended on specific serological tests during the initial period of pregnancy (before weeks 12–16 of gestation). The invasive (amniocentesis) and non-invasive (ultrasonographic examination) prenatal tests, carried out at 21 weeks gestation, revealed a severe CMV infection in a fetus small for gestational age with ventriculomegaly. The presence of overt ultrasound abnormalities combined with high viral load in the amniotic fluid sampled at the appropriate times was highly suggestive of an unfavourable prognosis. The autopsy performed on the fetus confirmed severe disseminated CMV infection with histological brain damage.